2020
DOI: 10.35371/aoem.2020.32.e17
|View full text |Cite
|
Sign up to set email alerts
|

Association between employment status and sickness presenteeism among Korean employees: a cross-sectional study

Abstract: Background Sickness presenteeism (SP) indicates “going to work while being ill.” The importance of SP has only recently been investigated, and the association between SP and employment status has been inconsistent across studies. Therefore, we conducted this study to explore the association between SP and employment status by using presenteeism propensity (PP), which can reflect the individual decision-making process. Methods The study population included employees part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Nurses with lengthy experience seemingly have a negative view of meeting workplace demands ( 8 ). Furthermore, nurses experience higher presenteeism with more frequent weekly over time, as previously reported ( 57 ). This suggested that managers should intervene to reduce presenteeism.…”
Section: Discussionsupporting
confidence: 75%
“…Nurses with lengthy experience seemingly have a negative view of meeting workplace demands ( 8 ). Furthermore, nurses experience higher presenteeism with more frequent weekly over time, as previously reported ( 57 ). This suggested that managers should intervene to reduce presenteeism.…”
Section: Discussionsupporting
confidence: 75%
“…Figure 1 shows the study flow. Table 1 shows respondents characteristics: the median age (interquartile range) was 42 (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) years; the proportion of women was 42.3% (1494); a total of 1020 desk workers (28.9%) had started working from home since or after April 2020; the proportion of desk workers working from home once a week or less, and two to three times a week or more in 2021 was 9% (319/3532) and 14.5% (513/3532), respectively, while in 2022, it was 8.4% (298/3532) and 13.8% (489/3532), respectively. Figure 2 depicts the transition of the work-from-home status.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…However, while sick workers tend to choose working from home, it is still unclear whether workers who recently started working from home are more likely to experience work functioning impairment at a later stage. In addition, although previous cross-sectional studies reported a wide range of socioeconomic disparity in the prevalence of working from home 33,34 and an employment status disparity in sickness presenteeism, 34 no evidence is available regarding the longitudinal difference of work functioning impairment among employment status types. Identifying the higher risk groups is important in taking effective measures.…”
mentioning
confidence: 99%
“…Job and workplace factors include aspects of the work environment such as job role demands and workplace policies. Previous findings suggest that presenteeism is associated with overtime, 7 employment status, 8 work format, 9 type of work, 10 ease of taking vacations, 11 and job stress (workplace support, job demands, and job control) 9,12 . Health and physical factors include existing (long‐term) health conditions and physical factors such as lifestyle‐related disease.…”
Section: Introductionmentioning
confidence: 99%